2021
DOI: 10.1002/jum.15620
|View full text |Cite
|
Sign up to set email alerts
|

Interobserver Agreement of Lung Ultrasound Findings of COVID‐19

Abstract: Background Lung ultrasound (LUS) has received considerable interest in the clinical evaluation of patients with COVID‐19. Previously described LUS manifestations for COVID‐19 include B‐lines, consolidations, and pleural thickening. The interrater reliability (IRR) of these findings for COVID‐19 is unknown. Methods This study was conducted between March and June 2020. Nine physicians (hospitalists: n = 4; emergency medicine: n … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 30 publications
0
30
0
1
Order By: Relevance
“…33 Several of the findings (especially B-lines) have excellent interrater reliability and can be expediently learned. 30,34,35 Based on the results of this study, a rapid assessment of the anterior lungs may provide sufficient risk stratification and warrants further study.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…33 Several of the findings (especially B-lines) have excellent interrater reliability and can be expediently learned. 30,34,35 Based on the results of this study, a rapid assessment of the anterior lungs may provide sufficient risk stratification and warrants further study.…”
Section: Discussionmentioning
confidence: 88%
“…We found that LUS has moderate-tosubstantial IRR for LUS among COVID-19 for the findings included in this study. 30 Based on our IRR findings, we developed an interpretation protocol. First, two researchers would independently apply the consensus guidelines (Appendix) to create a standardized approach to image interpretation.…”
Section: Scanning Protocol and Interpretationmentioning
confidence: 99%
“…The interrater agreement in detecting sub-pleural consolidations and pleural thickening resulted lower but substantial. 9 However, LUS was performed by trained medical doctors in an inpatient setting.…”
Section: Introductionmentioning
confidence: 99%
“…In a recently published study investigating interobserver agreement of LUS in COVID-19 (although without measuring intraobserver agreement), Kumar et al found lower agreement for consolidations, similar agreement for pleural thickening and higher agreement especially when assessing B-lines 18 . This is in line with our assumption that low agreement in B-Line quantification might be due to a lack in specific training as observers met for a one hour calibration session before grading in the aforementioned study.…”
Section: Discussionmentioning
confidence: 99%